Peningkatan aktivitas dan hasil belajar matematika melalui pembelajaran kooperatif tipe Think Pair Share di kelas VC SD Negeri 47 Jambi - Dewi Sutria (Universitas Syiah Kuala, 2019)
The purpose of this study are to increase students’ learning activities in the learning processof mathematics by applying the type of Think-Pair-Share (TPS) cooperative learning and toimprove students’ learning outcomes in mathematics. This research was carried out in thefifth grade Students in Elemntary School 47 Jambi during the first semester of 2017/2018Academic Year. The action was carried out in 2 cycles with the subject matter covered incycle I was about explaining and reducing two fractions with different denominators and incycle II about multiplication and division of decimal fractions. Data was collected byobservation methods using observation sheets and student learning outcomes was collectedusing tests. The results of the study based on data analysis showed an increase in learningoutcomes from 64.29% wich is sufficient category in the first cycle to be a good category inthe second cycle with 83.93%. For student learning outcome there was an improvement from50% with inactive categories to 90% with very active categories.. The results of this studyindicate that the application of the Think-Pair-Share (TPS) Cooperative Learning model canbe used to improve student learning outcomes.Keywords: learning process, Think-Pair-Share.